The education of social value in the attention to diversity conditions - Mancebo Calzado, Martha (2018)
There is necessary a change in the conception of the discipline, starting of the manifestations that come with bad social behaviors, in all the stages of human development. The saith that discipline represents in this work and it focus too in the meaning that reach the good fit of actions in students giving answers to demandings of the on activities for the common good ,as objective assume for them, with preventive way and in the attention to diversity. The attention to diversity in the formation of discipline as social value it result a principle to achieve results in this way, because we need to have in count the characteristics in the development of the stages of the student and how those manifest in a singular way each one. It represents then the configuration of the well-known process, that is finish in one educative strategy for the formation of discipline social value through a community scholar project that give guarantee and direction to important social behaviors, in function of good relationships on the different contexts of scholar development, starting with actions that make more powerful the relationships between school and community.